The effect of coping strategies on flourishing with self-compassion as a mediator in teachers with functional dyspepsia - Rusdah Parinduri; Suryani Hardjo; Salamiah Sari Dewi (Institute of Computer Science (IOCS), 2026)
The inability of teachers to manage stress effectively can worsen their health and trigger functional dyspepsia. This study aims to understand how teachers can achieve flourishing despite experiencing work-related stress. It examines the coping strategies used to manage stress and how these strategies contribute to achieving flourishing. This study also investigates the role of self-compassion in the relationship between coping strategies and flourishing. The purpose of this study is to examine the effect of coping strategies on flourishing, the effect of coping strategies on self-compassion, the effect of self-compassion on flourishing, and the effect of coping strategies on flourishing with self-compassion as a mediating variable among teachers with functional dyspepsia. This study employed a quantitative method by distributing questionnaires to 200 teacher respondents diagnosed with functional dyspepsia who met the screening criteria of the R4-FDDQ Functional Dyspepsia Diagnostic Questionnaire. Data analysis was conducted using JASP version 0.19.3.0 through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that the respondent data were reliable, valid, and the model demonstrated good fit. The findings reveal a significant relationship between coping strategies and flourishing, as well as between coping strategies and self-compassion. However, self-compassion did not have a significant effect on flourishing, nor did it significantly mediate the relationship between coping strategies and flourishing among teachers with functional dyspepsia. In coping with problems, teachers with functional dyspepsia tended to prioritize emotion-focused coping in achieving flourishing. Religiosity and mindfulness were identified as the most prioritized strategies compared to other aspects.